Tik Tok Application as A Learning Medium for Islamic Religious Education - Lilis Setiawati (EDUCARE: Jurnal Ilmu Pendidikan, 2023)
This study aims to explore the application of the TikTok application as a learning medium for Islamic Religious Education. This study uses a qualitative approach with a case study type. Data collection techniques were carried out through observation and interviews with grade VIII students who were the subjects of the study. The results of the study showed that the use of the TikTok application was able to increase the appeal of Islamic Religious Education learning through short video content that was presented creatively and relevant to students' lives. From a cognitive aspect, TikTok helps broaden students' insights into the Sirah Nabawiyah material. From an affective perspective, students showed interest and trust in religious content delivered by trusted figures in the video. Meanwhile, from a psychomotor aspect, students began to show changes in behavior that were more disciplined and participatory in learning activities. The implications of this study indicate that TikTok can be an innovative alternative in Islamic Religious Education learning, especially in presenting an approach that is in accordance with the characteristics of the digital generation. The use of social media such as TikTok is not only recreational, but can also be used productively to support educational goals, especially in shaping students' religious understanding and attitudes. Therefore, teacher training and policy development are needed that encourage the positive use of digital media in learning in schools